2021
DOI: 10.3892/etm.2021.10756
|View full text |Cite
|
Sign up to set email alerts
|

Gas6/Axl signaling pathway promotes proliferation, migration and invasion and inhibits apoptosis in A549 cells

Abstract: Several studies have demonstrated that growth arrest-specific protein 6 (Gas6) and Axl are highly expressed in various tumor tissues, such as renal cell and esophageal carcinoma. However, the effect of the Gas6/Axl signaling pathway on lung adenocarcinoma is still unclear. The aim of the present study was to investigate the effect of the Gas6/Axl signaling pathway on lung adenocarcinoma cells and its mechanism of action, which may provide a novel target for the clinical treatment of lung adenocarcinoma. Human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
3
3
0
Order By: Relevance
“…As we expected, 500 ng/ml Gas6 plus 1% FBS dramatically promoted the invasions of both IgR3 and WM852 ( Fig 3 ). These data provide a role for Gas6 in promoting melanoma invasion through a matrix barrier consistent with prior findings suggesting such a role [ 16 , 17 , 30 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As we expected, 500 ng/ml Gas6 plus 1% FBS dramatically promoted the invasions of both IgR3 and WM852 ( Fig 3 ). These data provide a role for Gas6 in promoting melanoma invasion through a matrix barrier consistent with prior findings suggesting such a role [ 16 , 17 , 30 ].…”
Section: Resultssupporting
confidence: 90%
“…We increased the concentration of dialyzed FBS in this assay due to extended time exposure and to optimize cell attachment and invasion through the MatriGel (S1 Fig) . As we expected, 500 ng/ml Gas6 plus 1% FBS dramatically promoted the invasions of both IgR3 and WM852 (Fig 3). These data provide a role for Gas6 in promoting melanoma invasion through a matrix barrier consistent with prior findings suggesting such a role [16,17,30].…”
Section: Plos Onesupporting
confidence: 90%
“…GAS6 contains 4 epidermal growth factor-like domains and 2 laminin globular-like domains that contain the interaction sites for its TAM (Tyro3, Axl, and Mer) receptor tyrosine kinases [ 33 ]. The GAS6/TAM system is involved in a variety of pathophysiological processes, such as apoptosis inhibition [ 34 , 35 ], inflammation inhibition [ 36 ], and oxidative stress [ 37 ]. Thus, we speculated that GAS6-AS2 might alleviate sepsis-related AKI in this way.…”
Section: Discussionmentioning
confidence: 99%
“…Oncology 2022;100:536-541 DOI: 10.1159/000525601 cells and, thus, metastasis [7,8]. In some cancer types, it could be demonstrated that a higher expression of Gas6 and Axl were associated with poorer survival [4].…”
Section: Gas6 In Chrcc 537mentioning
confidence: 99%
“…The presence of Gas6/TAM inhibits cell death and leads to proliferation of tumor cells [ 6 ]. Also, Gas6/TAM promotes migration of the tumor cells and, thus, metastasis [ 7 , 8 ]. In some cancer types, it could be demonstrated that a higher expression of Gas6 and Axl were associated with poorer survival [ 4 ].…”
Section: Introductionmentioning
confidence: 99%